2015
DOI: 10.1007/s00520-015-2980-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of Chinese patients with prostate cancer in comparison to general population and other cancer populations

Abstract: Patients with prostate cancer substantially perceived their HRQOL to be better, compared to patients with other cancers, with overall health, energy, and mental health below of Hong Kong general population. Interventions should target at these domains in order to improve the HRQOL of patients with prostate cancer. It is reassuring to find that prostate cancer had less negative impact on HRQOL than other cancer types did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…For example, both the investigators of the ProtecT trial and a review on prostate cancer and health-related quality of life, reported scores on the two SF-12 components in just diagnosed patients that were consistent with those in the population at large [ 5 , 7 ]. Moreover, according to other studies, just diagnosed with prostate cancer patients had lower scores on the emotional-psychological component with the respect to those in the general population [ 14 , 15 ]. Again, these results could be explained by the higher level of education of the participants in our sample compared to that of the general population, a factor that is usually associated to an overall better physical and emotional health.…”
Section: Discussionmentioning
confidence: 85%
“…For example, both the investigators of the ProtecT trial and a review on prostate cancer and health-related quality of life, reported scores on the two SF-12 components in just diagnosed patients that were consistent with those in the population at large [ 5 , 7 ]. Moreover, according to other studies, just diagnosed with prostate cancer patients had lower scores on the emotional-psychological component with the respect to those in the general population [ 14 , 15 ]. Again, these results could be explained by the higher level of education of the participants in our sample compared to that of the general population, a factor that is usually associated to an overall better physical and emotional health.…”
Section: Discussionmentioning
confidence: 85%
“…The psychometric properties of the Chinese version of the SF-12 v2 have been confirmed [15]. It has been widely used for patients with different types of cancer, such as prostate [16].…”
Section: Short-form-12 Health Survey Version 2 (Sf-12 V2)mentioning
confidence: 90%
“…Mean differences of the total scores, MCS, and PCS were about 22.4, 24.4 and 20.4, respectively, indicating that those living in Bandar Abbas had better HRQoL than those living in Tehran. Other studies conducted on the general population of China, Turkey, and Brazil (21,23,24) revealed a better score for HRQoL in all 8 domains, MCS, and PCS of SF-12 QoL. In some other studies (20,22-26), woman and older people had a lower score in QoL, therefore, policy-makers and clinicians should consider age and sex as the most important non-modifiable risk factors for reducing QoL.…”
Section: Discussionmentioning
confidence: 99%